2023
DOI: 10.18549/pharmpract.2023.3.2843
|View full text |Cite
|
Sign up to set email alerts
|

Parents of asthmatic children knowledge of asthma, anxiety level and quality of life: unveiling important associations

Arwa Nour,
Ahmad Alsayed,
Iman Basheti

Abstract: Purpose: Asthma in children affects millions around the world. Parents' knowledge of asthma and their quality of life (QoL) may affect the management of their asthma child. The study aimed to assess the knowledge of asthma, anxiety, and QoL of parents who have children diagnosed with asthma living in Amman, Jordan. Patients and methods: This cross-sectional study was conducted over five months in Amman, Jordan. Children with asthma were recruited from outpatient respiratory clinics. Parents were interviewed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Considering the earlier research results, which suggest that parents use a reactive asthma management style and control their child’s asthma by avoiding potential triggers [ 36 ], interventions aimed at parents’ knowledge regarding the PA of children with asthma are mandatory. One of the possible responses to parental anxiety and the associated behavior could be to increase asthma knowledge, since a recent study suggested poor knowledge of asthma in parents, also emphasizing that increasing asthma knowledge among parents is advised [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the earlier research results, which suggest that parents use a reactive asthma management style and control their child’s asthma by avoiding potential triggers [ 36 ], interventions aimed at parents’ knowledge regarding the PA of children with asthma are mandatory. One of the possible responses to parental anxiety and the associated behavior could be to increase asthma knowledge, since a recent study suggested poor knowledge of asthma in parents, also emphasizing that increasing asthma knowledge among parents is advised [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary Care: Collaboration among pulmonologists, primary care physicians, nurses, and pharmacists can improve guideline adherence and patient outcomes (17,18).…”
mentioning
confidence: 99%